Non-Indigenous Leaders’ Perceptions of their Leadership in K to 12 Nunavut Schools - Sharif, Shamimara (Werklund School of Education, 2024)
This case study explores non-Indigenous leaders’ perceptions of their leadership in kindergarten to grade twelve (K to 12) Nunavut schools. Educational leadership influences student achievements, including graduation, in schools of Indigenous communities (Odulaja & Halseth, 2018; Truth and Reconciliation Commission of Canada, 2015). Understanding the context that includes the social and historical circumstances of K to 12 Nunavut schools, perceptions the non-Indigenous educational leaders bring to the system, and the relationship between the two, is vital for non-Indigenous educational leaders in K to 12 Nunavut schools. Leaders’ perceptions of their leadership are also vital to educational pedagogy in schools as they influence their choices when leading. There is also insufficient research on non-Indigenous leaders’ perceptions of their leadership in K to 12 Nunavut schools. The following questions guided the study: How do non-Indigenous leaders perceive their leadership in K to 12 Nunavut schools? How do the beliefs and values of non-Indigenous leaders inform their leadership in K to 12 Nunavut schools? I approached the study through a qualitative case study methodology in keeping with Merriam’s (1998) interpretation. I gathered data using semi-structured interviews, reflective journals, and public records. The analysis of data reveals four main findings: (a) a necessity for understanding educational leadership from the perspective of Elders and Indigenous Knowledge Keepers, (b) the understanding of the continuity of colonial relations within the K to 12 Nunavut schools, (c) a necessity for Indigenous representation of their language, culture, and knowledge in K to 12 Nunavut schools, and (d) the importance of embedding Inuit Indigenous perspectives within the K to 12 Nunavut schools. The interpretation process highlights how I perceived my leadership, gaps in the K to 12 Nunavut education system, and the importance of Inuit Indigenous involvement in educational leadership in Nunavut to overcome the ...